Research on the generation mechanism and characteristics of an Energy Internet backbone network - Xiaopeng Li; Zheng Zhang; Yucheng Zhou; Peng Li; Liyan Ji; Liyan Ji (Frontiers in Physics, 2023)
The Energy Internet adopts the mechanism of “regional coordination and hierarchical control” to realize the clean power compatibility and reliability in power operation. In the network topology, the traditional tree network is transformed to the hierarchical partition network. First, this paper analyzes the topological features of “hierarchical control, intra-layer partition, interregional interconnection, and regional autonomy” of the Energy Internet. On this basis, the hierarchical ring network autonomy (HRNA) topological generation and evolution mechanism of the Energy Internet is proposed, and the different levels of a Beijing power grid framework are taken as an example to expand and evolve to the Energy Internet. Based on the comparison and analysis of the network characteristics constructed in this paper with relevant literature studies, this mechanism generates a network that is close to the Internet in terms of average degree, network diameter, and aggregation coefficient. However, there is no centrality node with a higher degree of nodes in the Internet topology, which better reflects the equivalence concept of the Energy Internet.